An Effective Controller Design Challenges for Autonomous Vehicle System – A Review - Dr. S. Srinivasan, T. S. Balaji (International Journal of Advanced Science and Technology, 2020)
This paper deals with various issues and challenges pertaining to the design of controller for the Autonomous vehicle system (AVS). The foremost problem is selection of controllers. In recent days, there are many controller like Embedded, Co-operative, Artificial intelligence, neural controllers, Fuzzy controllers, Adaptive Fuzzy controller (Type-I, Type-II etc.,). Even the available methodologies may be centralized or distributive controller. This paper mainly deals about the design of controller to face the challenges like some unpredicted things happens on the road and disturbances that occur from outside may produce the challenges in autonomous vehicles. Path tracking and Lane keeping with collision avoidance are the areas need to solve those challenges. Certain parameters like stiffness of the vehicle at the corner, Contact between road-tire, electrical/mechanical parts of the vehicle and speed of the vehicle degrade the overall performance. To identify with this issue the available techniques are taken for survey.